Construire et assurer l`héritage des Jeux olympiques et paralympiques. Pour une inclusion sportive durable des personnes vivant des situations de handicap? - Richard, R.; Marcellini, A.; Pappous, A. S.; Joncheray, H.; Ferez, S. (Movement & Sport Sciences - Science & Motricité, 2019)
Using the Olympic and Paralympic Games to build a more inclusive and inclusive society is at the heart of the "Paris 2024" project. Improving the visibility and sporting participation of disabled people is a strong ambition of the legacy of the Paralympic Games. The purpose of this article is to review research on the legacies of past Paralympic Games in order to consider the construction of the Paris 2024 legacy in terms of the inclusion of disabled people. We will focus more specifically on three dimensions of this heritage: the staging and the visibility of Paralympic athletes, the "leverage" effect of the Paralympic Games on sport participation and its coordination, and finally access to high-level sport for disabled people.